Health-related quality of life among adult patients with visual impairments in Yazd, Iran - Mehdi Raadabadi; Sara Emamgholipour; Rajabali Daroudi; Farzan Madadizadeh; Amirreza Veisi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Visual impairment (VI) is one of the major public health problems that cause suffering, disability, loss of productivity, and reduced quality of life (QoL). This study aimed to evaluate the health-related QoL (HRQoL) among adults with visual problems in 2021. Materials and Methods: This analytical cross-sectional study was conducted on 300 patients with VIs referring to ophthalmology centers in Yazd, Iran. Data were collected through face-to-face interviews using EQ-5D, visual analog scale (VAS), and demographic information questionnaires. The results were analyzed using independent sample t-test, one-way analysis of variance, Pearson correlation coefficient, and adjusted limited dependent variable mixture model (ALDVMM) model by STATA, and SPSS. RESULTS: The mean and standard deviation of EQ-5D-5 L index and EQ-VAS score in the studied patients were 0.68 ± 0.25 and 72.46 ± 19.36, respectively. Most problems at unable/extreme level were related to the mobility dimension (12%) and the usual activities dimension (9%). Factors related to HRQoL scores using ALDVMM model showed that divorced or widow marital status, age over 50, having strabismus, and acuter visual problems had significant negative effects on EQ-5D-5 L index values (P < 0.05). CONCLUSIONS: The results showed that HRQoL was moderate in patients with VIs and reduced in patients with high disease severity, old age, lack of a spouse, retirement, and nonuniversity education. As a result, socioeconomic and demographic characteristics were required to be considered in visual health policies.